Microstructural analysis of demineralized primary enamel after in vitro toothbrushing (Pesquisa Odontológica Brasileira, 2002)
The aim of this study was to investigate, in vitro, the morphological characteristics of demineralized primary enamel subjected to brushing with a dentifrice with or without fluoride. In order to do so, 32 enamel blocks were divided in 4 different groups containing 8 blocks each. They were separately immersed in artificial saliva for 15 days. The experimental groups were: C - control; E - submitted to etching with 37% phosphoric acid gel (30 s); EB - submitted to etching and brushing 3 times a day with a non-fluoridated dentifrice; EBF = submitted to etching and brushing 3 times a day with a fluoridated dentifrice. The toothbrushing force was standardized at 0.2 kgf and 15 double strokes were performed on each block. After the experimental period, the samples were prepared and examined under SEM. The control group (C) showed a smooth surface, presenting scratches caused by habitual toothbrushing. The etched samples (E) exhibited different degrees of surface disintegration, but the pattern of acid etching was predominantly the type II dissolution. The brushed surfaces were smooth, with elevations which corresponded to the exposure of Tomes process pits and depressions which corresponded to interrod enamel. Particles resembling calcium carbonate were found in the most protected parts of the grooves. No morphological differences were observed between brushing with fluoridated (EBF) and non-fluoridated (EB) dentifrice. The results suggest that the mechanical abrasion caused by brushing demineralized enamel with dentifrice smoothes the rough etched surface, and the presence of fluoride does not cause morphological modifications in this pattern.